The Influence of Marketing Strategy on Customer Satisfaction at PT Sumber Trijaya Lestari, Pekanbaru City - Arfi, Lingga Ramadhana; Manik, Anggi Harianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the influence of marketing strategy on customer satisfaction at PT Sumber Trijaya Lestari in Pekanbaru City. A marketing strategy is a company's effort to design and implement a marketing mix that includes product, price, distribution, and promotion in order to create added value for customers. This research uses a quantitative method with a survey approach. The population of the study consists of customers of PT Sumber Trijaya Lestari, with a sample size of 133 respondents and 10 indicators. Data were collected using a questionnaire and analyzed using simple linear regression.The results show that the t-test value for the marketing strategy variable (X) is 3.300, which is greater than the t-table value of 2.002, with a significance level of 0.004, which is less than 0.05. This means that the marketing strategy has a positive and significant effect on customer satisfaction at PT Sumber Trijaya Lestari in Pekanbaru City. This proves that the better the marketing strategy implemented by the company, the higher the level of customer satisfaction. The Adjusted R Square value (coefficient of determination) is 0.550, meaning that the marketing strategy can explain 55% of the variation in customer satisfaction, while the remaining 45% is influenced by other variables outside of this study. This indicates that customer satisfaction is not only affected by the marketing strategy but also by other factors such as product quality, service, price, customer trust, brand image, and previous experiences. These external factors can contribute to the level of customer satisfaction but were not examined in this research.